1998
DOI: 10.1002/aic.690440709
|View full text |Cite
|
Sign up to set email alerts
|

Hollow‐fiber‐based adsorbers for gas separation by pressure‐swing adsorption

Abstract: Hollow-fiber-based adsorbers for gas separation by pressure-swing adsorption (PSA) was studied experimentally. The high efficiency of hollow-fiber-based adsorbers for gas .separation was illustrated by hydrogen separation using fine-powder-activated carbon and molecular sieve as adsorbents. The adsorption equilibrium and dynamics of the hollow-fiber adsorbers were determined. The pressure drop of the gas flowing through the adsorbers was also examined. The adsorbers were tested for hydrogen separation from nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…Extrusion, treating HCl followed by water vapor treatment and pyrolysis in two steps at 600-1000 • C and compaction at 1200-2000 • C are the processes used in their production [10]. Microporous polypropylene hollow fibers filled with adsorbent particles have been successfully used separating hydrogen from nitrogen and carbondioxide [11]. Preliminary results of hollow fiber formation from water glass and metal salts and characterization of dried fibers study were reported by Balköse et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…Extrusion, treating HCl followed by water vapor treatment and pyrolysis in two steps at 600-1000 • C and compaction at 1200-2000 • C are the processes used in their production [10]. Microporous polypropylene hollow fibers filled with adsorbent particles have been successfully used separating hydrogen from nitrogen and carbondioxide [11]. Preliminary results of hollow fiber formation from water glass and metal salts and characterization of dried fibers study were reported by Balköse et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, adsorption columns use packed beds with inherent limitations such as a high mass transfer resistance [32], a high heat transfer resistance as well as undefined flow conditions. Fibrous sorbents promise to overcome fundamental shortcomings of TSA processes [33][34][35]. Feng et al [33] were the first to introduce a hollow fiber geometry which resulted in a lower pressure drop and a lower mass transfer resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Fibrous sorbents promise to overcome fundamental shortcomings of TSA processes [33][34][35]. Feng et al [33] were the first to introduce a hollow fiber geometry which resulted in a lower pressure drop and a lower mass transfer resistance. Controlled flow conditions in the laminar regime led to sharper breakthrough curves and thus higher recoveries [33].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason state of the art medical oxygen concentrators such as that invented by Appel et al (2004) now contain small zeolite beads (such as Zeochem Z12-07 LiLSX beads with a size distribution of 0.4-0.8 mm). Appropriate bead size is related to the bed size, with larger commercial fixed bed PSA devices generally having a bead size larger than 2-3 mm in equivalent diameter (Feng et al 1998).…”
Section: Introductionmentioning
confidence: 99%